Protein Immobilization on A Biotinylated Polymer Coating - Zhang, Jingzhe; Wang, Xintong; Liu, Limei; Chen, Peimin; Zhang, Xiaohong; Lu, Tiancheng (Asian Journal of Chemistry, 2012)
A polymer coating to specifically immobilize proteins was constructed from a biodegradable amphiphilic triblock copolymer, biotinylated poly(ethylene glycol)-b-poly(L-lactide)-b-poly(Llysine) (PEG-PLA-PLL/biotin), accompanied by covering it with a layer of blocking agent consisting of gelatin, poly(N-vinyl pyrrolidone) and casein. The bioactive surface was characterized by a confocal laser scanning microscope analysis by means of consecutive immobilization of non-labeled streptavidin, biotinylated rabbit antigoat monoclonal antibodies and FITC-labeled goat globulin. In results, the bioactive surface repelled nonspecific protein and allowed specific biotin-streptavidin interaction; meanwhile the immobilized streptavidin kept its bioactivity. In addition, the PEG-PLA-PLL/biotin coating could enhance the attachment and proliferation of mouse L929 fibroblasts, suggesting that it had excellent biocompatibility. The PEG-PLA-PLL/biotin is potential to become a bioactive material for protein immobilization and biodegradable scaffolds.